Children’s Responses to Problem-Based Picture Book (Preučevanje otroške in mladinske književnosti, 2025)
In this paper, based on the doctoral thesis (Višček 2024), we focus on defining the children's problem-based picture book, which is primarily related to specific themes that are difficult or complex for a child with limited literary competence (violence, addiction, gender identity, etc.). Other elements of a quality problem-based picture book include illustrations and stylistic devices (e.g., atmosphere, metaphors) that contribute to a demanding literary experience. To demonstrate the didactic interpretation of such picture books, we explore three Slovenian problem-based picture books that have been discussed in the 3rd grade of primary school: The Blue Honey (2020) by Cvetka Sokolov, The Girl and the Giant (2019) by Neli Kodrič Filipić, and First Love (2014) by Brane Mozetič. We present the key findings of our action research and highlight some key guidelines for reading problem-based picture books in literature classes that facilitate communication between pupils and the teacher as a reading model.